Removal Of Fats, Oils, And Grease From Food And Beverages Wastewater By Using Sono-Electrocoagulation Technique - Rusli, Muhammad Ikmal Ahmad (Universiti Sains Malaysia, 2022)
Fresh wastewater of municipal solid waste (MSW), is a form of high-strength organic wastewater, so often likely lead to quick and huge bioactivity of microorganisms. Fresh wastewater (FW) typically classified as a dangerous and extremely contaminated wastewater. Thus, this research targeted to investigate treatment of fresh wastewater from Municipal Solid Waste by Sono-Electrocoagulation process with dual application of Iron and Iron electrodes for maximize the removal of COD and oil and grease. The influence of temperature (30 °C ,40 °C and 50 °C), pH (7.0–9.0), and working period (0– 60 min) on the treatment of wastewater were studied to achieve optimal treatment efficiency. The maximum removal efficiencies of oil and grease and chemical oxygen demand (COD) under influenced of temperature were obtained as 87% and 92%, respectively, at the pH 6 (initial pH),temperature 50 °C, and reaction time of 30 min . Under controlled by pH maximum removal efficiencies of oil and grease and chemical oxygen demand (COD) were achieved as 96 % and 83 % , respectively, at the pH 7,temperature 30 °C (initial condition), and reaction duration of 30 min. There were decline in the percentage removals of the parameters after achieving an optimum parameters. This is may relate to the particle size size becones more significant with increasing reaction time. Hence, the particles’ energy level rises, and the coagulation rate of the particles lowers. Sono-electrocoagulation is proven to be effective in fresh wastewater treatment and environmental friendly approach for total pollutant removal.